This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Stirling's approximation is lo g n ! = n lo g n − n + O ( n ) ; so lo g n ! n 2 1 = n 1 lo g n − n 1 + O ( n 1 ) → 0 as n → ∞ ; hence the limit is 1 .
Let y = n → ∞ lim ( n ! ) n 2 1 Therefore ln y = n → ∞ lim n 2 1 r = 0 ∑ n − 1 ln ( n − r ) ln y = n → ∞ lim n 2 ln n − n 1 r = 0 ∑ n − 1 n 1 ln ( 1 − n r ) ln y = 0 − n → ∞ lim n 1 ∫ 0 1 ln ( 1 − x ) d x ln y = 0 − n → ∞ lim n 1 ( − 1 ) ln y = 0 − 0 y = e 0 = 1
Alternate: ( n ! ) n 2 1 ≤ ( n n ) n 2 1 ≤ n n 1 → 1
For the alternate solution you are saying that L = ( n ! ) n 2 1 ≤ ( n ) n 1 ≤ 1 , hence the limit L is less than equal to 1 however, how does this prove that the limit is 1 , since you haven't bounded the limit L on both sides, nor have you used sandwich theorem successively.
n 2 1 tends clearly to 0 (for n grows up to infinity). And a n y t h i n g E l s e T h a n Z e r o 0 = 1 . Thus the answer is 1.
Is this way of thinking wrong, and fortunatly leads to the correct answer in this case? And if it is wrong, why ? I'm a little bit confused, because all answers are way more complicated than this one.
wrong thinking ...try this ( 1 + n ) 1 / n when n tends to infintity
Problem Loading...
Note Loading...
Set Loading...
L = n → ∞ lim ( n ! ) n 2 1 = n → ∞ lim ( 2 π n ( e n ) n ) n 2 1 = n → ∞ lim ( 2 π ) 2 n 2 1 e − n 1 n n 1 + 2 n 2 1 = n → ∞ lim n n 1 + 2 n 2 1 = n → ∞ lim exp ( ( n 1 + 2 n 2 1 ) ln n ) = exp ( n → ∞ lim ( n ln n + 2 n 2 ln n ) ) = exp ( n → ∞ lim ( 1 n 1 + 4 n n 1 ) ) = e 0 = 1 By Stirling’s formula: n ! ∼ 2 π n ( e n ) n A ∞ / ∞ case L’H o ˆ pital’s rule applies Differentiate up and down w.r.t. n
References :